(untitled) (Sustainable Development Insights, 2026)
The rapid development of logistics startups in Indonesia has created dynamic working environments that require employees to maintain high levels of productivity while adapting to flexible work systems. This study aims to analyze the impact of flexible work arrangements and mental health on employee productivity in logistics startups in Indonesia. A quantitative research approach was employed using a survey method. Data were collected from 250 employees working in logistics startup companies through structured questionnaires measured using a Likert scale. The collected data were analyzed using Statistical Package for the Social Sciences (SPSS) version 25, including descriptive statistics, validity and reliability tests, and multiple linear regression analysis. The results of the study indicate that flexible work arrangements have a positive and significant effect on employee productivity. In addition, mental health also shows a positive and significant influence on employee productivity. The coefficient of determination shows that flexible work arrangements and mental health jointly explain 42.5% of the variation in employee productivity. These findings suggest that organizations that provide flexible working systems and support employee psychological well-being are more likely to achieve higher productivity levels. This study contributes to the literature on human resource management in startup environments and provides practical insights for logistics startups in developing strategies to enhance employee performance and organizational sustainability.